2008
DOI: 10.1001/archneurol.2008.2
|View full text |Cite
|
Sign up to set email alerts
|

Pain as a Nonmotor Symptom of Parkinson Disease

Abstract: To determine whether pain is more frequent among people with Parkinson disease (PD) than among age-matched controls.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
165
3
3

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 224 publications
(180 citation statements)
references
References 12 publications
9
165
3
3
Order By: Relevance
“…Our findings are similar to previous studies [1,3]. However, the frequency of dystonic pain in our study was lower than that previously reported [1,3,25]. Variation in the prevalence of the pain subtype may be related to the definition of pain, inclusion criteria, or differences in the patient population among the centers.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Our findings are similar to previous studies [1,3]. However, the frequency of dystonic pain in our study was lower than that previously reported [1,3,25]. Variation in the prevalence of the pain subtype may be related to the definition of pain, inclusion criteria, or differences in the patient population among the centers.…”
Section: Discussionsupporting
confidence: 86%
“…In our study, the prevalence rate of chronic pain was 74.1%, which was within the range of previous reports (40-85%) [1,3,25,26]. The pathophysiology of pain in PD is multifactorial.…”
Section: Discussionsupporting
confidence: 86%
“…9) One of the reasons is considered to be the decreased threshold of pain due to abnormality of the dopaminergic system in the basal ganglia of PD patients. 5,10) Administration of anti-parkinsonian medication 5,14) or DBS 16,20,23) results in increased pain thresholds.…”
Section: Introductionmentioning
confidence: 99%
“…In advanced stages, pain may be caused by motor fluctuations (dyskinesia or off-period dystonia), and may be radicular or due to musculoskeletal problems [27,28]. In most of the published work, pain in PD was found to be related to a musculoskeletal cause or dystonia [1,3,29,30,31,32]. Musculoskeletal pain (44.4%) and dystonia-related pain (19.1%) were the most common types of pain (table 4).…”
Section: Discussionmentioning
confidence: 99%